Analyzing the Development of Russia’s Agricultural Sector to Identify Import Needs and Product Range - Mikhail Tolmachev; Aleksandr Tsypin; Elena Gerasimova (Journal of Global Innovations in Agricultural Sciences)
Under the sanctions, Russian agricultural producers face challenges related to the differing degrees of dependency of agricultural sectors on imports. This article identifies the agro-industrial sectors that are most dependent on imported products. Using statistical methods and qualitative content analysis of the corresponding scientific literature, the authors summarize research results on the share of imports in the Russian agro-industrial complex. The study identifies the agricultural sectors most dependent on imports. Particularly in vegetable and fruit cultivation, sectors like tomato and cucumber farming are highly import-dependent due to limited domestic production capabilities. The authors emphasize that import dependency should not be measured solely by the availability of certain agricultural products on the Russian market. It is also essential to consider the share of imports in the seeds and eggs required for production, animal feed, and agricultural machinery. Seeds emerge as the most problematic area. However, the authors note the positive impact of Russian policies aimed at reducing import dependency, particularly regarding the provision of hatching eggs. Dependency in this area has decreased by 90% due to efforts by the Ministry of Agriculture of the Russian Federation. In conclusion, after highlighting the most import-dependent areas, the authors stress the importance of investing in these sectors. To mitigate these dependencies, policy recommendations include enhancing domestic seed production, increasing investment in local agricultural technologies, and strengthening public-private partnerships to boost local production capacities. Keywords: Agri. food sector, agricultural trade, market analysis, import policy, international corporations.